FAKTOR-FAKTOR YANG MEMPENGARUHI PERINGKAT OBLIGASI PADA PERUSAHAAN NON KEUANGAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Muhammad Andi Faradi; Supriyanto Supriyanto (Ekonomi dan Bisnis, 2015)
This study was conducted to examine the effect of variable Liquidity, Capital Structure, and Profitability of the rating on the bonds of non-financial companies listed on the Indonesia Stock Exchange 2012 period. The population in this study contained a number of 151 companies in Indonesia Stock Exchange in 2012 and has a period of bond ratings of PT. Valuation in 2013. The sampling technique used was purposive sampling. In order to obtain a total sample of 44 companies. Data were obtained from published financial statements of the company's website the Indonesia Stock Exchange is www.idx.co.id results of this study indicate that simultaneous variables Liquidity, Capital Structure, and Profitability significant effect on the bond rating. While the results of research conducted partially indicates that liquidity variables significantly influence bond rating, capital structure does not significantly affect the bond rating. While other variables in this study are Pofitabilitas significantly influence bond rating.